Preliminary Analysis for Development of Google Sites Web-Based Learning Media - Susanti; Rita Fitriani (Jurnal Pendidikan Matematika, 2023)
Learning media plays an important role in helping the smooth process of learning activities carried out, including when studying the Multivariable Calculus course. The purpose of this study is to analyze student needs for teaching materials in the form of Google-Sites Web-based learning media that can be accessed easily anywhere and can help students understand learning materials in the Multivariable Calculus course. This research is a qualitative descriptive study with the research subject being the third-semester students of the Mathematics Education study program at the Raja Ali Haji Maritime University. The research data were collected through observation sheets of lecture activities and questionnaires on student needs for teaching materials in the form of Multivariable Calculus learning media which were distributed via the google form link. The results of observations indicate that there are no available learning media that is attractive, can be accessed easily, and can be used as a guide in the learning process in Multivariable Calculus courses such as the Google-Sites Web. The results of the questionnaire analysis show that students need learning media in the form of Websites Google in the Multivariable Calculus course. Based on the research data, it can be concluded that it is necessary to develop learning media in the form of Websites Google.